Sistem Monitoring Kamar Tidur Pintar dan Suhu Berbasis IoT dengan Cisco Packet Tracer - Wirasih, Ni Made Ayu; Suhartana, I Ketut Gede (Jurnal Nasional Teknologi Informasi dan Aplikasnya, 2024)
This research endeavors to develop an Internet of Things (IoT)-based smart bedroom monitoring system, leveraging Cisco Packet Tracer technology as a robust simulation platform. The system facilitates automatic monitoring and management of indoor environment parameters such as temperature, security, and lighting settings, aiming to enhance occupants' comfort and safety. Key components of the system include a temperature sensor, microcontroller, and an LCD information screen, enabling real-time display of bedroom temperature data. System validation was conducted via simulations using Cisco Packet Tracer, consistently demonstrating the system's efficacy in automating room temperature monitoring and management. These findings lay a solid groundwork for advancing IoT technology, emphasizing deeper integration, addressing challenges, proposing solutions, and exploring potential applications across diverse contexts.